2016
DOI: 10.1515/roe-2015-1007
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Changing Tastes: Approaches to Explaining Unstable Individual Preferences

Abstract: Standard economic theory assumes individual preferences to be fixed and exogenously given. This view has been challenged by numerous empirical observations. In reaction to those challenges, economic theory has been modified, mostly by including additional arguments into individuals' utility functions. Among the approaches that tackle preference change are new consumer theory, habit formation, interdependent and status preferences, social and emotional influences, and reference point-dependent preferences. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 311 publications
(239 reference statements)
0
5
0
Order By: Relevance
“…that people make identical decisions in identical repetitions of the decision task. If behavior varies with repetition, these variations are usually attributed to strategic considerations such as reputation building or to some form of learning from information feedback (for an overview, see [ 12 ]). But what do the dynamics of social behavior look like if these considerations are excluded?…”
Section: Introductionmentioning
confidence: 99%
“…that people make identical decisions in identical repetitions of the decision task. If behavior varies with repetition, these variations are usually attributed to strategic considerations such as reputation building or to some form of learning from information feedback (for an overview, see [ 12 ]). But what do the dynamics of social behavior look like if these considerations are excluded?…”
Section: Introductionmentioning
confidence: 99%
“…Note: Friedman (1953) pointed out that "unrealistic assumptions in models are not per se problematic. The quality of a model should be judged from the exactness of its predictions concerning the purpose of its creation rather than from the reality of its assumptions" (Jacobs, 2016). 6.…”
Section: Notesmentioning
confidence: 99%
“…3 -Information on University Education was provided as an aggregate measure. 4 -Level 7 and 8 (ISCED). 5 -Non-Available Information.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Understanding individuals' preferences in this context is extremely important as the efficacy of contingency measures depended heavily on individuals' behaviours. Literature has shown that it is challenging to capture these preferences [3,4]. To overcome this, researchers have been increasingly using Discrete Choice Experiments (DCE) to understand preferences and inform policy decisions, which is especially relevant in healthcare studies [5].…”
Section: Introductionmentioning
confidence: 99%